Implikasi Pedagogis Pada Sakramen Perjamuan Kudus Dalam Liturgi Gereja - Sumiyati Sumiyati; Eriyani Mendrofa (Evangelikal: Jurnal Teologi Injili dan Pembinaan Warga Jemaat, 2021)
The Lord's Supper is one of the sacraments of the church and is an important part of the Christian liturgy. The author conducts research on the meaning of the Holy Communion so that he can find pedagogical implications in the Holy Communion. The research used is a literature analysis approach that uses various relevant literature sources. The pedagogical implications of the Lord's Supper concern the past, present and future. The meaning of the past means that the Lord's Supper is a reminder of Christ's sacrifice for believers. Today means that the Lord's Supper means sharing in enjoying the benefits of Christ’s death and fellowship with the members of the body of Christ, even Christ himself. The meaning of the future means that the Holy Communion is a guarantee of enjoying the Kingdom of Heaven and the great supper in the future. The Lord's Supper is an expression of hope for His return. Christ Jesus is the sure hope. Practically speaking, Holy Communion reminds us of the importance of fellowship with fellow members of the body of Christ. ABSTRAKPerjamuan Kudus merupakan salah satu sakramen gereja dan menjadi bagian penting dalam liturgi Kristen. Penulis melakukan penelitian terhadap makna perjamuan kudus sehingga dapat menemukan implikasi pedagogis dalam perjamuan kudus. Penelitian yang digunakan adalah pendekatan analisis pustaka yang menggunakan berbagai sumber pustaka relevan. Implikasi pedagogis Perjamuan Kudus menyangkut masa lalu, masa kini dan masa yang akan datang. Makna masa lalu berarti bahwa Perjamuan Kudus merupakan peringatan pengorbanan Kristus bagi orang percaya. Masa kini berarti bahwa Perjamuan Kudus memiliki makna keikutsetaan menikmati keuntungan kematian Kristus serta persekutuan dengan anggota tubuh Kristus, bahkan Kristus sendiri. Makna masa yang akan datang berarti bahwa Perjamuan Kudus menjadi jaminan menikmati Kerajaan Sorga dan perjamuan agung di masa yang akan datang. Perjamuan Kudus merupakan perwujudan pengharapan akan kedatangan-Nya kembali. Kristus Yesus adalah pengharapan yang pasti. Secara praktis, Perjamuan Kudus mengingatkan tentang pentingnya persekutuan dengan sesama anggota tubuh Kristus.